Natural Food Additives and Preservatives for Fish-Paste Products: A Review of the Past, Present, and Future States of Research - Khawaja Muhammad Imran Bashir; Jin-Soo Kim; Jeong Hyeon An; Jae Hak Sohn; Jae-Suk Choi (Journal of Food Quality)
Fish-paste products, also known as fish cakes or surimi-based products, are worldwide favorites. Surimi, a wet protein concentrate of fish muscle, is used as an intermediate raw material to produce surimi seafood. The flavor, texture, taste, shelf-life, and market value of surimi-based products depend on the source of the fish meat, type of applied heat treatment, and additives used to prepare the surimi. While preparing surimi with chemical additives, several problems have been observed, such as a lack of unique characteristics, inferior acceptability, and poor functionality. Various types of fish-paste products have been developed by using different ingredients (e.g., vegetables, seafood, herbs and oriental medicines, grains and roots including carrots, and functional food materials). However, a systematic review of fish-paste products prepared using natural food additives has not yet been performed. Therefore, the quality characteristics of fish-paste products and their functionalities were elucidated in this study. With the increasing demand for surimi seafood products, the functional properties, physiochemical properties, and shelf-life of surimi-based products need to be improved. This review will aid the preparation of new value-added products in the surimi industry.